Case report: Cytopenias in VEXAS syndrome - a WHO 2022 based approach in a single-center cohort - Diral, Elisa; Campochiaro, Corrado; Tomelleri, Alessandro; Bergonzi, Gregorio M.; Pizzano, Umberto; Ponzoni, Maurilio; Bongiovanni, Lucia; Ronchi, Paola; Tresoldi, Cristina; Rigamonti, Silvia; Scarfò, Federico; Latino, Gloria M.; et al. (Frontiers in Immunology, 2024)
VEXAS syndrome is an acquired autoinflammatory disease characterized in most cases by cytopenias and macrocytic anemia. Dyshematopoiesis is a frequent finding in chronic inflammatory conditions and therefore, cytopenias are not easily classified in VEXAS patients. Here we report a series of 7 patients affected by VEXAS associated cytopenias, treated at our center. The use of NGS, together with morphological assays, integrated with the WHO 2022 criteria, allowed to identify three subsets of VEXAS associated cytopenias: ICUS (idiopathic cytopenia of uncertain significance), CCUS (clonal cytopenia of uncertain significance) at high risk of clonal evolution, and MDS. This approach could help to better understand the nature of VEXAS associated cytopenias and to guide the use of specific targeted treatments in order to achieve long lasting responses.